Financial ratio: performance of PN4 companies / Mohd Fariz Abu Khalid - Abu Khalid, Mohd Fariz (2007)
Financial distress diagnosis and prediction has been a focal issue in finance due to its importance on the operation of a firm, its environment and the economy. The focus and discussion of this issue is becoming more relevant in the aftermath of the Asian financial crisis in 1997. To measure and predict the financial distress, this study examine the linkages between financial ratios and PN4 company that been listed on Bursa Malaysia. The ratio measured based on information disclosed in the financial statements of 60 companies that been listed from year 1997-2000. The study identifies the relationship between PN4 companies and financial ratios which 4 types of ratios will be use namely as quick ratio, debt ratio, net profit margin and return on equity that acts as independent variables. The data was used to predict the significant effect of the independent variables on determining the failures or the financial distress of PN4 companies between the years 2001-2002. This study proceeded with statistical test which is logistic regression model in order to indicates and predict the financial distress of PN4 companies. The study found that there is an inconsistency results and prediction of PN4 companies. This result implies that there are some of the ratios failed to indicate the failures of the PN4 companies.